Influence of prebreeding progesterone plus prostaglandin F2-α on estrus and fertility in lactating dairy cows - M.O. Mee; R.E. Stewart; Jeffrey S. Stevenson; Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1987)
Progesterone administered before breeding may increase estrous expression and subsequent fertility in lactating dairy cows. Holstein cows (n=302) were assigned randomly at calving to three groups. Cows received no treatment (controls), one injection of prostaglandin F 2-α (PGF), or progesterone plus one injection of PGF (PRID + PGF). The average interval to estrus was 5 days shorter in PRID + PGF cows compared to cows given only PGF. In addition, more cows were observed in estrus 2 to 5 days after treatment in the PRID + PGF group compared to the PGF group. Average days from calving to conception were reduced in PRID + PGF cows by 15 to 20 days compared to control and PGF cows. We concluded that prebeeding progesterone in combination with PGF appears to enhance fertility.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Progesterone; Prostaglandin F2-α; Fertility; Lactation